Faktor-Faktor Sistem Admisi yang Berhubungan dengan Kepuasan Pasien yang Pertama Kali Dirawat di RSUD X - Norsehan Norsehan; Achir Yani S. Hamid; Muhammad Anshari (Syntax Idea)
In a service institution such as a hospital, there is a significant correlation between service and patient satisfaction, this is an important component as information in efforts to improve hospital services. The patient admission process is often considered the front-line experience in healthcare facilities. A positive first impression between staff and patient is important to ensure a positive patient experience. Patient acceptance standards starting from the registration of new patients need to pay attention to the factors of staff acceptance, reception methods, pleasant waiting rooms, effective waiting times and handing over of patients to the treatment room. The purpose of this study was to obtain an overview of the relationship between factors (reception staff, patient admissions, waiting room conditions, waiting time, and the handover process with patient satisfaction. The study design was descriptive correlational, with a cross sectional study approach, looking at the influence of the admission system on patient satisfaction.A total sample of 82 respondents, taken using purposive sampling technique. Through the process of identifying and calculating the results of the study, the majority of respondents were satisfied with the admission process, and there was a significant relationship between the admission process (acceptance of staff, method of admission, waiting room, waiting time, and handover) with patient satisfaction. The results of the analysis on all satisfaction dimensions (tangible, reliable, responsiveness, assurance, and empathy) have a value lower than the 0.05 significance level, indicating a strong relationship between the admission process and patient satisfaction. Thus, from the results of the study in this study, it was found that in all aspects which include: reception, reception method, waiting room, waiting time and patient acceptance have an effect on patient satisfaction.